Seasonal distribution and correlation between IL-10 and IL-13 gene polymorphism and their expression in scabies-infected patients: Cytokine gene polymorphism in scabietic patients - Farhad Bilal, Eman; Jawdah Bilal, Samir; Hasan Azeez, Sarhang (Cellular and Molecular Biology, 2024)
Scabies is a significant concern in global health. It is more prevalent in individuals who have poor hygiene and live in crowded conditions, hence, it is seasonal distribution and immunological response in Erbil population is the aim of the present study. In the Erbil Dermatology Education Centre in Erbil, Iraq, 154 patients were recruited for the research between April 2022 and March 2023. If a patient has a suspicious skin lesion and itching for a minimum of one week, scabies may be considered. Blood samples were collected from each participant in the study to evaluate serum levels of IL-10 and IL-13, then the DNA was isolated to study the gene polymorphism for the mentioned cytokines. Results showed that female 60.3% were more infected than male 39.6%. The median age of participants was (10 - >51) years, among infested, adolescents aged 10-20 years displayed the highest rate (31.8%). The carriers of GA genotype of IL-10 were protective against the infection, OR:0.61. while the TT carriers of IL-13 were susceptible to scabies infection with OR:2.14. IL-10 GA genotype was more prevalent in male patients OR:2.14 whereas the AA genotype was most protective in females OR:0.32. the IL-13 CT genotype was protective for males with OR:0.52. Both of IL-10 and IL-13 serum levels were increased significantly with infection and highest levels were found in wild homozygous genotypes (GG and CC) and lowest ratio was found in mutant homozygous genotypes of IL-10 and IL-13 respectively. Point mutation in IL-10 GA was protective and wild TT genotype of IL-13 was susceptible to the scabies infection. Double mutation in IL-10 AA was protective to females and single mutation of IL-13 CT was protective to males.